Corrigendum: Artificial neural network model to predict student performance using nonpersonal information (Front. Educ., (2023), 8, (1106679), 10.3389/feduc.2023.1106679) - Chavez, Heyul (2023)
n the published article, the Acknowledgment Statement was mistakenly not included in the publication. The missing statement appears below: Acknowledgments “The authors would like to thank the Research Directorate of the Universidad Peruana de Ciencias Aplicadas for the support provided to carry out this research work through the UPC-EXPOST-2023-1 incentive.” The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.